Tripled troubles on financial, social, and sexual needs of female conflicts with three time shifts working at garment industries in Indonesia - Giyoto, Giyoto; Inderasari, Elen; Ulfiana, Elita; Mahsusi, Mahsusi; Adi Nur Alfisyahri, Khoirul (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2023)
This study aims to investigate the problems of financial, social, and sexual aspects of working females in labour force with the three-time shift system in Indonesia. Working females, as a matter of, are responsible for both household and working duties from which they are highly potential to face various problems. This case study interviewed (either in group or individual) and observed 150 randomly selected respondents of working females from garment industries in Surakarta and Yogyakarta Indonesia. Data triangulation technique of observation and interview were to firm the trustworthiness. The data were analysed interactively as suggested by Miles and Huberman: data reduction, data display, and conclusion drawing. The findings showed that the majority of the respondents participated in the labour force due to their family financial problem. Though the financial problem was reduced, being a working female in three-time shift system brought about the other problems, such as social and sexual problems. The females could fulfil the family financial needs by sacrificing the social and sexual fulfilments of the family because they had no time and physical energy anymore. These problems were commonly found from the respondents, although it was found several variables that vary the level of the problems from each individual and group.